2017
DOI: 10.4236/jdm.2017.73014
|View full text |Cite
|
Sign up to set email alerts
|

Research of Type 2 Diabetes Patients’ Problem Areas and Affecting Factors

Abstract: Background: The study was descriptively conducted in order to determine problem areas and the affecting factors among the Type II diabetes patients. Methods: The study was carried out between August and October, 2011 in the Endocrinology Polyclinic in Adiyaman, Turkey. The population of the study was made up by Type II diabetes patients who were diagnosed with diabetes at least one year ago and came to Endocrinology Polyclinics at the study period. The sample of the research consisted of 188 patients who were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(13 reference statements)
0
1
0
1
Order By: Relevance
“…Masalah kesehatan yang saat ini sedang terjadi yaitu double burden disease dimana terdapat peningkatan kejadian penyakit tidak menular/ degenerative yang diikuti dengan peningkatan kejadian penyakit menular. Salah satu penyakit tidak menular yang saat ini mengancam keberlangsungan hidup manusia yaitu diabetes mellitus (Notoatmodjo, 2003(Notoatmodjo, , 2007 (Alzaman and Ali, 2016;Başkan and Tan, 2017;Eibl et al, 2017) Jurnal Manajemen Informasi Kesehatan Indonesia Vol. 7 No.1 Maret 2019ISSN: 23372337-585X (Printed); DOI : 10.33560/jmiki.v7i1.216 Hasil uji statistik pada tabel 2 diketahui bahwa ratarata LOS pasien diabetes mellitus yang PJK lebih tinggi yaitu 11.26 hari dengan variasi 7.64 hari, dibandingkan dengan LOS pasien diabetes mellitus tidak PJK yaitu 9.80 hari dengan variasi 7.77 hari.…”
Section: Hasil Dan Pembahasanunclassified
“…Masalah kesehatan yang saat ini sedang terjadi yaitu double burden disease dimana terdapat peningkatan kejadian penyakit tidak menular/ degenerative yang diikuti dengan peningkatan kejadian penyakit menular. Salah satu penyakit tidak menular yang saat ini mengancam keberlangsungan hidup manusia yaitu diabetes mellitus (Notoatmodjo, 2003(Notoatmodjo, , 2007 (Alzaman and Ali, 2016;Başkan and Tan, 2017;Eibl et al, 2017) Jurnal Manajemen Informasi Kesehatan Indonesia Vol. 7 No.1 Maret 2019ISSN: 23372337-585X (Printed); DOI : 10.33560/jmiki.v7i1.216 Hasil uji statistik pada tabel 2 diketahui bahwa ratarata LOS pasien diabetes mellitus yang PJK lebih tinggi yaitu 11.26 hari dengan variasi 7.64 hari, dibandingkan dengan LOS pasien diabetes mellitus tidak PJK yaitu 9.80 hari dengan variasi 7.77 hari.…”
Section: Hasil Dan Pembahasanunclassified
“…in lifestyle causing social, psychological, emotional as well as psycho-social problems as one has to bring a lot of changes in their habits or in daily activities. International Diabetes Federation (IDF) reported that in 2011, there were 356 million diabetic people in the world and was estimated that it would increase to 552 million people by 2030, thus in the 21 st century, it is considered as one of the most challenging health problems 7 . Considering the prevalence of DM in India, it is reported that in 2000, the prevalence of patients with DM was 31 million in India which are expected to reach 79 Million by 2030 8 .…”
Section: Overview Of Diabetes Mellitus With Diagnostic Criteriamentioning
confidence: 99%